Ex Situ Limb Perfusion System to Extend Vascularized Composite Tissue Allograft Survival in Swine. Issue 10 (October 2015) - Ozer, Kagan; Rojas-Pena, Alvaro; Mendias, Christopher L.; Bryner, Benjamin; Toomasian, Cory; Bartlett, Robert H.
<x xml:space="preserve">Abstract</x> Background Organ perfusion systems have successfully been applied in solid organ transplantations. Their use in limb transplantation and replantation has not been widely investigated. In this study, we tested the potential for ex situ perfusion system to prolong limb allograft viability in a swine forelimb amputation/replantation model. Methods Fourteen swine were used. In group 1 (n = 4), we perfused 4 amputated limbs for 12 hours using warm (27°C–32°C) autologous blood. Group 2 (n = 3) served as a cold preservation control group, preserving limbs for 6 hours at 4°C. All limbs were transplanted into healthy swine (n = 7) and observed for another 12 hours. Hemodynamic variables of circulation, as well as perfusate gases and electrolytes (pH, pCO2, pO2, O2 saturation, Na+, K+, Cl−, Ca2+, HCO3−, glucose, lactate) were measured. Muscle samples were used to measure single-muscle fiber contractility. Results In the control group, no microcirculation was observed after 6 hours of cold storage. In the pump perfusion group, all limbs displayed a gradual increase in lactate levels (P < 0.05) during ex situ perfusion that returned to normal after transplantation and reperfusion (P = 0.05). The pH and potassium remained stable throughout the experiment. Single-muscle fiber contractility testing showed near normal contractility at the end of the reperfusion period (P > 0.05). Limb weight did not increase significantly between the end of pump perfusion and reperfusion (P > 0.05). Conclusions We demonstrated the potential to preserve limb allograft using ex vivo circulation. This approach promises to extend the narrow time frame for revascularization of procured extremities in limb transplantation.